Peningkatan Literasi Herbal Melalui Edukasi Penggunaan Herbal yang Tepat pada Siswa SMA Abdurrab Islamic School - Arnila Melina; Indrawan Indrawan; Elvina Zuhir; Fahmi Nofriandi; Helga Pasadena (Jurnal Informasi Pengabdian Masyarakat, 2026)
The use of herbal medicine in Indonesia continues to increase alongside growing public interest in traditional healthcare practices. However, inadequate knowledge regarding the appropriate use of herbal products may result in irrational practices, including improper indications, incorrect dosages, and potential interactions with conventional medicines. Adolescents are an important target group for early health education to promote informed and responsible decisions regarding herbal use. This community service program aimed to enhance herbal literacy by educating students at Abdurrab Islamic School Senior High School on the safe and appropriate use of herbal medicine. The activity was conducted on 9 May 2026 and involved 40 students through interactive lectures, educational media presentations, group discussions, and question-and-answer sessions. The educational materials covered the definition of herbal medicine, its benefits and limitations, safe use principles, possible adverse effects, herb–drug interactions, and the importance of obtaining information from reliable sources. The program was well received, with participants actively engaging throughout the sessions and demonstrating improved understanding of evidence-based and safe herbal use. The interactive discussions also enhanced students’ ability to critically evaluate health information related to herbal products. This educational intervention is expected to encourage healthier behaviors and strengthen adolescents’ awareness of the rational, safe, and responsible use of herbal medicine in daily life.